Barrier properties of poly(lactic acid)/cloisite 30B composites and their relation between oxygen permeability and relative humidity. Issue 5 (14th September 2016) - Bartel, Melanie; Remde, Helmut; Bohn, Andreas; Ganster, Johannes
ABSTRACT: Poly(lactic acid) based nanocomposite films were prepared by melt compounding and subsequent flat film extrusion. After characterizing the nanocomposites with the help of transmission electron microscopy and wide angle X‐ray diffraction to estimate the nanoclay distribution in the matrix material, the oxygen and water vapor permeability of untreated and annealed nanocomposite films were analyzed. A reduction to 34% of both permeability values could be realized by the addition of 6 wt % Cloisite 30B and subsequent annealing to realize maximum crystallinity. Experimental permeability as a function of nanoclay concentration was successfully described by the Tortuous Path Model. In addition, the correlation between oxygen permeability and relative humidity was analyzed for pure PLA and PLA based nanocomposite films. For both untreated films oxygen permeability decreased almost linearly between 0% and 96% RH to approximately 70% of the respective value for the dry sample. Annealed PLA films, on the other hand, showed a similar behavior up to 70% RH but an increase in oxygen permeation for higher moisture content. This is explained by the observed reduction in crystallinity generating more free volume, bringing the system closer to the amorphous case where permeability is generally higher. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44424. Abstract :